Effect of prosthetic design and restorative material on the stress distribution of implant-supported 3-unit fixed partial dentures: 3D-FEA - Ahmed, Mohamed Abdel; Hamdy, Amina Mohammad; Fattah, Ghada Abdel; Elfadl, Ahmed Khaled Abo (Brazilian Dental Science, 2022)
Objective: Evaluate the effect of Implant prosthetic designs and restorative material on the stress concentration of 3-unit implant-supported restoration with two restorative materials. Material and Methods: Six different screw-retained prostheses models were virtually designed and divided according to design: fixed bridge (FB), cantilever bridge (CB), and separate crowns (SC). Then, each model was also divided into two subgroups according to the material: Ultra-translucent multi-layered zirconia (Kuraray Noritake Dental Inc., Japan); or a combination of PEEK (Polyetheretherketone) framework (BioHPP, Bredent, GmbH & Co., KG, Germany) and zirconia (ZR) crowns (ultra-translucent multi-layered zirconia, Kuraray Noritake Dental Inc., Japan). A vertical load of 100 N was applied statically perpendicular to the central fossa of each crown. The von-Mises stress was computed using Solidworks software (SolidWorks Corp, Massachusetts, USA), based on the physical parameters of the materials. Results: FB showed the lowest von Mises stress values out of all 3 design models. Moreover, the combination of PEEK and zirconia showed strain values smaller than full zirconia. The highest von Mises stress value was recorded in CB with the zirconia subgroup at (1098 MPa) while the lowest von Mises stress value was recorded in FB with combined PEEK and zirconia subgroup at (190 MPa). Conclusion: For three-unit implant supported restorations, the use of PEEK framework and zirconia crowns was found to be more favorable biomechanically regarding the prosthetic components, implant and bone stresses. KEYWORDS Biomechanics; Dental implants; Implant prosthetic designs; Finite element analysis; CAD/CAM.